Color change of different dual-cure resin cements after thermocycling = Cambio de color de diferentes cementos de resina de curado doble después del termociclaje - Atay, Ayşe
The purpose of this study is to evaluate the effect of thermocycling on the color change of the amine-free dual-cure resin cements. IPS e.max CAD blocs were cut into specimens of 1 mm thickness (N=28) and cemented with one of the 4 different amine-free dual-cure resin cements (NX3 Nexus [NX], Kerr Dental; Variolink Esthetic DC [VE], Ivoclar Vivadent; Panavia V5 [PV], Kuraray Dental; G-CEM Linkforce [GC], GC Corporation) (n=7). A spectrophotometer was used for color measurements. Specimens were subjected to thermocycling (5°C and 55°C; 5000 and 10000 cycles). Normality of data distribution was tested by using the Kolmogorov-Smirnov test. Statistical analysis was performed using a two-way analysis of variance (ANOVA) and Tukey's multiple comparison tests at a significance level of p<0.05. ∆E values were significantly influenced by the resin cements and the cycle periods (p<0.05). There were no significant differences between NX and VE groups after 5000 thermocycling, however after 10000 thermocycling VE group showed higher ∆E1 values than NX group (p>0.05). There were no statistically significant differences between the ∆E0 and ∆E1 values of the GC group, however the other groups were affected after 10000 thermocycling (p>0.05). Amine-free resin cements used for cementation showed color change after thermocycling except GC group. All resin cements were showed clinically acceptable color change after thermocycling (∆E<3.5).